Revealing the Potential Impacts of English-Medium Instruction (EMI) in Indonesian Higher Education Context - Muhammad Arif Al Hakim (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
In recent years, many top universities from non-English countries have been implemented English Medium Instruction (EMI) in teaching and learning processes because it provides beneficial impacts for institutions, lecturers, and students. However, some other countries do not support EMI implementation because it has several drawbacks that are ineffective for educational systems. This conceptual review article aims to promote the benefits of EMI implementation and suggest the better application of EMI in Indonesian higher education. The research methodology used in this investigation is a critical literature review. The concept used in this paper is to critically explore the potential implementation of EMI in Indonesian higher education, which aims to teach specific content subjects through English as a medium of instruction. This implementation promotes students’ bi-literacy and bilingual skills and their learning motivations to be highly capable of competing in the globalization era. As a result, the implementation of EMI expands three benefits that can be attained by the students and lecturers; EMI enhances academic competence, improves English proficiency level, increases motivation in the learning process. This critical paper proves that EMI implementation will significantly benefit Indonesian institutions, especially their students and lecturers.